Novel human reovirus isolated from children and its long-term circulation with reassortments - Yamamoto, Seiji P. (Sci Rep, 2020)
Mammalian orthoreovirus (MRV), also known as reovirus, was discovered in the 1950s and became the first reported segmented double-stranded RNA virus. MRVs have since been found in a variety of animal species, including humans. However, reports on MRV infections are scarce due to the rarity of their symptomatic occurrence. In Japanese surveillance studies, MRVs have been detected as gastrointestinal pathogens since 1981, with a total of 135 records. In Osaka City, Japan, MRV was first isolated in 1994 from a child with meningitis, and then in 2005 and 2014 from children with gastroenteritis. Here, we conducted the first molecular characterization of human MRV isolates from Japan and identified a novel human reovirus strain belonging to MRV type 2, designated the MRV-2 Osaka strain. This strain, with all three isolates classified, is closely related to MRV-2 isolates from sewage in Taiwan and is relatively close to an MRV-2 isolate from a bat in China. Our data suggest that the MRV-2 Osaka strain, which has circulated amongst humans in Japan for at least two decades, has spread internationally.